Pengembangan Insektisida Organik dari Ekstrak Daun Tembakau sebagai Solusi Ramah Lingkungan: Studi Kasus di Desa Ngusikan - Susanti, Ambar; Qomariah, Umi Kulsum Nur; Zuhria, Siti Aminatuz; Anandita, Septian Ragil; Prasdianto, Ryvaldi; Janah, Miftahul; Agustin, Putri; Muna, Laila Nailil; Rahayu, Any Puji (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This community service article explores the development of organic insecticides derived from tobacco leaf extract as an environmentally friendly solution for farmers in Ngusikan Village. The primary objective is to reduce the dependency on chemical pesticides, which pose significant health risks and environmental pollution. Through training sessions and direct practice, farmers learned the process of producing natural pesticides, gaining awareness of the benefits of sustainable agriculture. The results indicate increased farmer knowledge and willingness to utilize organic pesticides, with notable reductions in chemical pesticide usage. This program also highlights the economic potential of processed tobacco products, enhancing local income opportunities. As an outcome, Ngusikan Village serves as a model for sustainable agriculture by leveraging local resources for eco-friendly pest control.